Cysteine mutagenesis improves the production without abrogating antigenicity of a recombinant protein vaccine candidate for human chagas disease. Issue 3 (4th March 2017) - Seid, Christopher A.; Jones, Kathryn M.; Pollet, Jeroen; Keegan, Brian; Hudspeth, Elissa; Hammond, Molly; Wei, Junfei; McAtee, C. Patrick; Versteeg, Leroy; Gutierrez, Amanda; Liu, Zhuyun; Zhan, Bin; et al.
ABSTRACT: A therapeutic vaccine for human Chagas disease is under development by the Sabin Vaccine Institute Product Development Partnership. The aim of the vaccine is to significantly reduce the parasite burden of Trypanosoma cruzi in humans, either as a standalone product or in combination with conventional chemotherapy. Vaccination of mice with Tc24 formulated with monophosphoryl-lipid A (MPLA) adjuvant results in a Th1 skewed immune response with elevated IgG2a and IFNγ levels and a statistically significant decrease in parasitemia following T. cruzi challenge. Tc24 was therefore selected for scale-up and further evaluation. During scale up and downstream process development, significant protein aggregation was observed due to intermolecular disulfide bond formation. To prevent protein aggregation, cysteine codons were replaced with serine codons which resulted in the production of a non-aggregated and soluble recombinant protein, Tc24-C4. No changes to the secondary structure of the modified molecule were detected by circular dichroism. Immunization of mice with wild-type Tc24 or Tc24-C4, formulated with E6020 (TLR4 agonist analog to MPLA) emulsified in a squalene-oil-in-water emulsion, resulted in IgG2a and antigen specific IFNγ production levels from splenocytes that were not significantly different, indicating that eliminating putative intermolecular disulfide bonds had no significant impact on the immunogenicity of the molecule. In addition, vaccination with either formulated wild type Tc24 or Tc24-C4 antigen also significantly increased survival and reduced cardiac parasite burden in mice. Investigations are now underway to examine the efficacy of Tc24-C4 formulated with other adjuvants to reduce parasite burden and increase survival in pre-clinical studies.